Funcionalidad familiar y el rendimiento académico de los estudiantes de Octavo Año de Educación General Básica, de la Unidad Educativa “José Ángel Palacio”, periodo lectivo 2022-2023 - Díaz Mera, Elena Del Pilar (2023)
The present research work entitled: "Family Functionality and Academic Performance of Eighth Grade Students from “Educación General Básica”, at “Unidad Educativa José Ángel Palacio”, Academic Year 2022-2023," had as its general objective to analyze the family functionality in students' academic performance. To achieve this, a mixed-method approach was employed, allowing for qualitative and quantitative analysis, investigation, and data collection to address the stated objectives. The research design used was non-experimental, where the study subjects were assessed within their natural context without altering any situations. This was done by administering the Family Functionality Test to a population and sample of 50 representatives of eighth-grade students. To assess academic performance, the grade point average was analyzed, which is standardized by “Ministerio de Educación del Ecuador”. The most relevant results indicate that 52% of the investigated households fall under the classification of dysfunctional families, with an additional 14% considered severely dysfunctional. This latter group constitutes 66% of the total research population. Regarding academic performance, 62% of eighth-grade students are close to achieving the required learning outcomes (PAR). Therefore, it is necessary to undertake actions focused on identifying and intervening in the families of students with family dysfunction, to prevent their academic performance from being affected in the future. Keywords: Family, functionality, academic performance, alternative approach